EMR-P for small rectal neuroendocrine tumors: is it a preferred treatment?. (2nd December 2022) - Liu, Zhaohui; Zheng, Chunsi; Ding, Shihua; Chen, Chong; Yang, Jingbo; Wu, Ruinuan; Sun, Dayong
Abstract: Background: The selection of endoscopic treatments for small rectal neuroendocrine tumors is controversial. Objective: To retrospectively compare the effectiveness and safety of precut endoscopic mucosal resection (EMR-P) and endoscopic submucosal dissection (ESD) for small rectal neuroendocrine tumors (NETs). Methods: Data from 98 patients with small rectal NETs who were hospitalized at Shenzhen Second People's Hospital between August 2014 and November 2021 were collected. The en bloc resection rate, pathological complete resection rate, radical resection rate, operation time, adverse event rate and hospital stay were compared between the two groups. Results: The operation time in the EMR-P group was significantly shorter than that in the ESD group. The median hospital stay in the EMR-P group was also significantly shorter than that in the ESD group. There were no significant differences between the two groups in terms of the en bloc resection, complete resection or radical resection rates. There was also no significant difference in the incidence of adverse events between the two groups. The delayed bleeding and delayed perforation rates of the two groups were improved after conservative treatment without surgery. There was no significant difference in the rate of positive vertical margins and horizontal margins between the EMR-P group and the ESD group. No local recurrence or metastasis was found during follow-up. Conclusion: EMR-P is an effective and safe endoscopic treatment for rectal NETs with a diameter of less than 10 mm. EMR-P is a significantly shorter procedure and requires a shorter hospital stay than ESD. EMR-P does not increase the cut margin positivity rate.